The Assimilation and Integration Rights for Prisoners as Over Capacity Prevention Effort in the Covid-19 Pandemic - Saharuddin Saharuddin; Mawardi De La Cruzz; Haritsah Haritsah; Rahmawati Rahmawati; Rommi Y Hiola (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
Overcapacity Prisons in Indonesia are currently at an alarming stage, including the Class II A Gorontalo Prison, data shows that the prison population is 475 inmates while the prison can only accommodate 330 inmates. Such conditions are worrying in the midst of the COVID-19 pandemic, considering that the process of spreading this virus is so fast and can be transmitted to anyone. So that in the context of preventing and dealing with Covid-19, it is impossible to implement social restrictions in prisons, for example the application of social distancing. Various efforts have been made by the government to break the chain of the spread of this virus, with the issuance of Minister of Law and Human Rights No. 10 of 2020 and Kepmenkumham No. 19 of 2020 to ensure the safety of prisoners in prisons, but in reality, it has drawn criticism and caused its own unrest in the community. The specific purpose of this research is to find out and analyze the implementation of granting assimilation and integration rights for prisoners and to find out the form of anticipating strategies for overcapacity of Class II A Gorontalo prisons during the Covid-19 pandemic. The type of research used is empirical research, namely research with field data as the main data source, such as the results of interviews and observations. The results of this study indicate that (1) the implementation of granting assimilation and integration rights for prisoners is based on the regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 10 of 2020 and the Decree of the Minister of Law and Human Rights of the Republic of Indonesia No. M.HH-19 PK.01.04.04 of 2020. (2) The strategy to anticipate over capacity by the Class II A Gorontalo Penitentiary During the Covid 19 Pandemic was taken in several stages: a) Orientation Admission, b) Orientation Assimilation, c) Orientation Integration, and d) Assimilation.